Adjustment to COVID-19 Lockdown Among Italian University Students: The Role of Concerns, Change in Peer and Family Relationships and in Learning Skills, Emotional, and Academic Self-Efficacy on Depressive Symptoms - Calandri, Emanuela; Graziano, Federica; Begotti, Tatiana; Cattelino, Elena; Gattino, Silvia; Rollero, Chiara; Fedi, Angela (Frontiers in Psychology, 2021)
In Italy strict containment measures against COVID-19 pandemic were implemented from March to May 2020 with home confinement and schools and universities closed. Students shifted to remote learning, experienced a forced isolation from peers and an increased sharing of time and spaces with the family. The influence of these aspects on the psychological adjustment of university students is largely unexplored. This paper was aimed at investigating the role of some correlates of depressive symptoms specific to the lockdown condition experienced by young university students, namely contagion concern, perceived worsening of family, and peer relationships and perceived worsening of learning skills. Moreover, the possible mediating effects of emotional and academic self-efficacy in these relationships were examined. Data were collected from 296 Italian university students (aged 18–25 years; 83% female students) through an online survey by means of a snowball sampling methodology in May 2020. Significant depressive symptoms were reported by 67% of participants. Contagion concerns were related to depressive symptoms through the mediating effect of emotional self-efficacy. Worsening of learning skills was related to depressive symptoms through the mediating effect of academic self-efficacy. Depressive symptoms were directly related to worsening of family relationships but unrelated to worsening of peer relationships. Results are discussed in relation to the need of preventive interventions for this specific population in view of academic activities planning in the post-COVID 19 period.